Knobloch syndrome caused by homozygous frameshift mutation of the COL18A1 gene in a Chinese pedigree - Lu-Si Zhang; Hai-Bo Li; Jun Zeng; Yan Yang; Chun Ding (International Journal of Ophthalmology, 2018)
AIM: To explore the clinical feature and genetic etiology of a Chinese Knobloch syndrome family. METHODS: Ocular examinations and magnetic resonance imagings (MRIs) were performed on the family. Whole exome sequencing was conducted on the two patients. Sanger sequencing was utilized to validate the presence of variation in the family as well as in 100 normal controls. Real-time quantitative polymerase chain reaction (PCR) was used to detect the expression level of COL18A1 in peripheral blood lymphocytes of the patients and normal carriers. RESULTS: The affected subjects presented with vision loss, exotropia, cataracts, retinal detachment, and other complications. A homozygous c.4759_4760delCT (p.Leu1587ValfsX72) mutation (rs398122391) in COL18A1 was identified in the two patients, cosegregating with the phenotypes, and did not be detected in 100 normal controls. This mutation caused significant decreased expression of COL18A1 mRNA in the patients. CONCLUSION: The findings strongly indicate that this mutation is the disease-causing mutation. Moreover, this is the first Knobloch syndrome pedigree reported in the Chinese population.